2005
DOI: 10.1002/clc.4960281207
|View full text |Cite
|
Sign up to set email alerts
|

Markers of inflammation in acute coronary syndromes: Association with increased heart rate and reductions in heart rate variability

Abstract: These observational data, while limited, are the first to link autonomic tone and in particular sympathetic tone (as indicated by HRV), to the process of acute leukocytosis and systemic inflammation common in acute coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
2
33
1
1
Order By: Relevance
“…Decreased HRV has been reported in a variety of clinical settings associated with increased production of inflammatory cytokines (6,(22)(23)(24)31). Circulating levels of inflammatory cytokines are increased in patient with cirrhosis (19,55) and positively correlate with the severity of hepatic encephalopathy in this patient population (19,43,44).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Decreased HRV has been reported in a variety of clinical settings associated with increased production of inflammatory cytokines (6,(22)(23)(24)31). Circulating levels of inflammatory cytokines are increased in patient with cirrhosis (19,55) and positively correlate with the severity of hepatic encephalopathy in this patient population (19,43,44).…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to the predictions of the classical concept of homeostasis, the output of a wide variety of physiological systems, such as the normal heart beat, fluctuates in a complex manner, even under resting conditions (1,21). Deceased variability or increased regularity of the cardiac rhythm has been reported in different clinical settings associated with systemic inflammation and increased production of inflammatory cytokines, such as sepsis, diabetes mellitus, ischemic heart disease, congestive heart failure, and hepatic failure; in these contexts, it is a negative predictor of outcome (5,6,(22)(23)(24)31).…”
mentioning
confidence: 99%
“…6,29 There is indirect support for association of cardiac autonomic function and thrombosis. Physical exercise and psychological stress influence markers of fibrinolysis in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any apparent relationship between RR interval and CD 40 -L in the recovery phase might reflect of previously documented associations between generalized vascular inflammation and HRV. 6,29 Why the association is not evident during acute events might reflect low sensitivity in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…The SAA level is sometimes increased in hyperglycemic subjects (11,12). Several prior studies have indicated a positive correlation between the HRs and C-reactive protein (CRP), another inflammatory marker (13,14). However, these studies did not focus on hyperglycemia, and there has been an observation that SAA is closer to CVD-related pathologies than other markers, such as CRP (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%